Tingkat Kepuasan Peternak Terhadap Program Pelatihan Budidaya Lebah Madu di Sentra Peternakan Lebah Madu Flora Nauli Kabupaten Simalungun - Octaviana Tesalonika Krisanti Sagala; Siti Azizah (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study was to determine the profile of respondents, the implementation of the Honey Bee Cultivation Training program and the level of farmer satisfaction with the Honey Bee Cultivation Training program. The samples used were 30 breeder samples and data collected by using. Data analysis uses the Index Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods. The results of this include the characteristics of respondents who took part in the training, the majority of people of productive age were breeders aged 41-50 years as much as 37%. In terms of gender, the majority is male, 83%, which is because the breeders who take part in the Honey Bee Training program are not only from Simalungun Regency, but several breeders come from outside the city of Simalungun Regency. At the educational level, it was found that Bachelor graduates dominated the number by 60%. This is also related to the respondents' farming experience, several respondents who have more than 30 years of farming experience have high creativity and innovation in making stups or bee boxes using cement to prevent theft of beehives. Based on the calculation of the Customer Satisfaction Index (CSI), the performance or service value provided by officers of the Flora Nauli Center Honey Bee Cultivation Training program in Simalungun Regency was 73,15. The CSI Value Criteria explains that the value of 73,15 is in the